Vendor's optimal inventory policy with dynamic and discrete demands in an infinite time horizon. (December 2016) - Afzalabadi, Maryam; Haji, Alireza; Haji, Rasoul
Highlights: We study inventory policy in a supply chain with one vendor and several retailers. Vendor faces discrete demand in dynamic quantities in an infinite time horizon. Developing a heuristic algorithm (OPP) to find the vendor's optimal inventory policy. OPP results are absolutely more efficient in comparison with others in literature. We have shown that the inventory cost per time unit has a fading oscillation behavior. Abstract: Although inventory control under discrete demand in dynamic quantities and time intervals are very common in reality, existing literature has largely ignored them. In this paper, we investigate the inventory control decisions in a two echelon supply chain consisting of one vendor and several retailers. The vendor supplies a product to several retailers, who buy discrete quantities in pre-determined time intervals. The order quantity and order cycles for each retailer can be different from others. Vendor orders the required quantity from supplier and it will be immediately received at the vendor's warehouse. In this system, shortage is not allowed for the vendor. The transportation time from the supplier to the vendor is assumed to be zero and the supplier has enough stock that would never face shortages. We have developed a new efficient, greedy algorithm to find the optimal ordering policy involving the scheduling and the order quantity of vendor to his supplier to minimize his cost function over an infinite time horizon.